2008
DOI: 10.4103/1319-3767.37794
|View full text |Cite
|
Sign up to set email alerts
|

Serum retinol binding protein as an indicator of vitamin A status in cirrhotic patients with night blindness

Abstract: Background/Aim:Vitamin A deficiency is known to be associated with night blindness. Plasma retinol binding protein (RBP) estimation highly correlates with plasma retinol concentration to predict vitamin A status. Serum RBP estimation is reasonably simple, inexpensive, and highly applicable in less technologically developed settings. We studied the correlation of plasma vitamin A levels (by RBP estimation) and ocular manifestation in patients with liver cirrhosis.Materials and Methods:This prospective, cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…On the other hand, it was revealed that serum RBP level showed significant discrimination between patients with recalcitrant warts and healthy control groups ( P ≤ 0.001) at a cutoff value ≤1034.6 μ g/ml with sensitivity and specificity at 100% each. This finding is consistent with and supportive of the previous observation regarding low serum RBP as a reliable indicator of retinol deficiency . As retinol is crucial to the normal development of immune cells including neutrophils, monocytes, macrophages, NK cells, B cells, and T cells, both innate and adaptive cell‐mediated immunity are important for the elimination of HPV infection …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, it was revealed that serum RBP level showed significant discrimination between patients with recalcitrant warts and healthy control groups ( P ≤ 0.001) at a cutoff value ≤1034.6 μ g/ml with sensitivity and specificity at 100% each. This finding is consistent with and supportive of the previous observation regarding low serum RBP as a reliable indicator of retinol deficiency . As retinol is crucial to the normal development of immune cells including neutrophils, monocytes, macrophages, NK cells, B cells, and T cells, both innate and adaptive cell‐mediated immunity are important for the elimination of HPV infection …”
Section: Discussionsupporting
confidence: 92%
“…Vitamin A (retinol) is transported to the tissues in the form of retinol bound to RBP in a 1 : 1 complex. Plasma RBP concentrations highly correlate with plasma retinol as they exist in the circulation in equimolar concentrations with 93% sensitivity for predicting marginal vitamin A status and 91% sensitivity for predicting vitamin A deficiency; the corresponding specificities are 75 and 94%, respectively . RBP is less photo‐ and heat‐sensitive than retinol, where laboratory and refrigeration facilities are poor, and more accurate results may be obtained by measuring RBP rather than retinol concentrations as an indicator of vitamin A status …”
Section: Introductionmentioning
confidence: 99%
“…Some studies in Pakistan validated the efficacy of vitamin A-fortified cookies, and promising results were achieved for baking and storage stability of the product, thus suggesting fortification of cookies with retinyl acetate (14,68,69). However, the selection and levels of appropriate fortificant need to be particularly considered for fortification, e.g.…”
Section: Vitamin a Deficiency: Risks And Opportunitiesmentioning
confidence: 97%
“…Increased risk of blindness was assessed in North West Frontier Province of Pakistan (NWFP) among children aged 6 years or less (9,10), and 16% of the anaemic children in primary schools in Karachi, Pakistan, were shown to be vitamin A-deficient. The risk of VAD in Pakistan is around 70% in pregnant and lactating mothers (11-14). …”
Section: Introductionmentioning
confidence: 99%
“…RBP is responsible for the transport of vitamin A from liver to plasma 19 . The situation was reversed in liver when protein intake was more due to excess transport of vitamin A from liver to plasma.…”
Section: Discussionmentioning
confidence: 99%